2020
DOI: 10.1101/2020.05.18.099507
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Afucosylated immunoglobulin G responses are a hallmark of enveloped virus infections and show an exacerbated phenotype in COVID-19

Abstract: 27IgG antibodies are crucial for protection against invading pathogens. A highly conserved N-28 linked glycan within the IgG-Fc-tail, essential for IgG function, shows variable composition in 29 humans. Afucosylated IgG variants are already used in anti-cancer therapeutic antibodies for 30 their elevated binding and killing activity through Fc receptors (FcγRIIIa). Here, we report that 31 afucosylated IgG which are of minor abundance in humans (~6% of total IgG) are specifically 32 formed against surface epito… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
77
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(79 citation statements)
references
References 29 publications
2
77
0
Order By: Relevance
“…Previously, we and others have shown that anti-Spike IgG of severe COVID-19 patients has aberrant fucose and galactose expression, both compared to the total IgG within these individual patients, as well as compared to anti-Spike IgG from mild or asymptomatic patients (26,27). For a subset of COVID-19 serum samples in the present study, the glycosylation pattern of anti-Spike IgG1 had been determined previously for the study of Larsen et al (26), which showed significantly decreased fucosylation and increased galactosylation of anti-Spike IgG compared to total IgG within the tested patients (IgG glycosylation of the sera used in this study is depicted in Figure S2A). When plotting the percentage of anti-Spike IgG fucosylation against pro-inflammatory cytokine production, we observed an inverse correlation for IgG fucosylation and production of IL-1β, IL-6, and TNF ( Figure 3B), while this was not seen for IL-8 and IL-10 ( Figure S2B).…”
Section: Main Textmentioning
confidence: 79%
See 4 more Smart Citations
“…Previously, we and others have shown that anti-Spike IgG of severe COVID-19 patients has aberrant fucose and galactose expression, both compared to the total IgG within these individual patients, as well as compared to anti-Spike IgG from mild or asymptomatic patients (26,27). For a subset of COVID-19 serum samples in the present study, the glycosylation pattern of anti-Spike IgG1 had been determined previously for the study of Larsen et al (26), which showed significantly decreased fucosylation and increased galactosylation of anti-Spike IgG compared to total IgG within the tested patients (IgG glycosylation of the sera used in this study is depicted in Figure S2A). When plotting the percentage of anti-Spike IgG fucosylation against pro-inflammatory cytokine production, we observed an inverse correlation for IgG fucosylation and production of IL-1β, IL-6, and TNF ( Figure 3B), while this was not seen for IL-8 and IL-10 ( Figure S2B).…”
Section: Main Textmentioning
confidence: 79%
“…One of the key characteristics that determines IgG pathogenicity is glycosylation of the IgG Fc tail at position 297 (24,25). Previously, we and others have shown that anti-Spike IgG of severe COVID-19 patients has aberrant fucose and galactose expression, both compared to the total IgG within these individual patients, as well as compared to anti-Spike IgG from mild or asymptomatic patients (26,27). For a subset of COVID-19 serum samples in the present study, the glycosylation pattern of anti-Spike IgG1 had been determined previously for the study of Larsen et al (26), which showed significantly decreased fucosylation and increased galactosylation of anti-Spike IgG compared to total IgG within the tested patients (IgG glycosylation of the sera used in this study is depicted in Figure S2A).…”
Section: Main Textmentioning
confidence: 96%
See 3 more Smart Citations